2023
DOI: 10.3390/molecules28031417
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of RNF168 in Tumor Progression

Abstract: RING finger protein 168 (RNF168) is an E3 ubiquitin ligase with the RING finger domain. It is an important protein contributing to the DNA double-strand damage repair pathway. Recent studies have found that RNF168 is significantly implicated in the occurrence and development of various cancers. Additionally, RNF168 contributes to the drug resistance of tumor cells by enhancing their DNA repair ability or regulating the degradation of target proteins. This paper summarizes and prospects the research progress of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
4
1
Order By: Relevance
“…However, UbcH5c barely makes contact with the nucleosomal histone surface, and the lack of specific interactions between UbcH5c and the substrate may allow UbcH5c to efficiently ubiquitinate multiple substrates by pairing with different E3 ligases (e.g., RNF168 6 , Ring1B/Bmi1 55 and BRCA1/BARD1 56 ). Previous studies have suggested that the histone H2A α1 extension helix (16)(17)(18)(19)(20)(21)(22) plays a critical role in RNF168 activity 22 , whereas we did not observe direct engagement of UbcH5c with this helix in our structures.…”
Section: Interactions Of Ubch5c and Nucleosomal Dnacontrasting
confidence: 95%
See 1 more Smart Citation
“…However, UbcH5c barely makes contact with the nucleosomal histone surface, and the lack of specific interactions between UbcH5c and the substrate may allow UbcH5c to efficiently ubiquitinate multiple substrates by pairing with different E3 ligases (e.g., RNF168 6 , Ring1B/Bmi1 55 and BRCA1/BARD1 56 ). Previous studies have suggested that the histone H2A α1 extension helix (16)(17)(18)(19)(20)(21)(22) plays a critical role in RNF168 activity 22 , whereas we did not observe direct engagement of UbcH5c with this helix in our structures.…”
Section: Interactions Of Ubch5c and Nucleosomal Dnacontrasting
confidence: 95%
“…Dysfunction or mutations of RNF168 have been strongly implicated in the development and progression of various human diseases, including tumours such as breast and esophageal cancers 16 , as well as RIDDLE syndrome 17 , a novel human immunodeficiency and radiosensitivity disorder associated with defective DNA double-strand break repair. Consequently, mechanistic studies targeting RNF168 ubiquitination have garnered significant attention due to their profound biological and clinical implications 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…It is not uniform that the distribution of lipophilic monomer, hydrophilic monomers along the polymer chain. 35 The morphology and polymerization process of other selfpolishing resin emulsions are the same.…”
Section: Analysis Of Latex Particle Morphology and Polymerization Pro...mentioning
confidence: 99%
“…RNF168 has another role downstream of DDR in DSB repair by substituting for BRCA1 in BRCA1 and 53BP1 null cells [ 71 , 74 ]. High RNF168 expression levels have been observed in breast cancer and esophageal cancer [ 75 , 76 ], as well as genetic alterations in human papilloma virus (HPV)-positive head and neck cancer [ 77 ]. It is also commonly discussed concerning PARPi resistance [ 71 , 78 ].…”
Section: E3 Ligases As Novel Targetsmentioning
confidence: 99%